PENGARUH PERSEPSI PELAKU USAHA TENTANG AKUNTANSI, PENGETAHUAN AKUNTANSI, DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH - Ketut Tanti Kustina; Luh Putu Sri Utami (Journal of Financial and Tax, 2022)
Keywords: (MSME Perception, Accounting Knowledge, Business Scale, Accounting Information) Economic development of a country is one of the efforts to increase the economic level of its population. One indicator that describes the success of economic development in a country, among others, is the decline in the number of poor people. This study aims to determine the positive effect of Business Actor Perceptions about Accounting, Accounting Knowledge, and Business Scale on the Use of Accounting Information in Micro, Small and Medium Enterprises in North Denpasar District. This research design uses quantitative research methods. The data collection technique used is the questionnaire method. The population in this study were all MSME actors in North Denpasar who were recorded in the MSMEs assisted by the Denpasar City MSME Cooperative Service, namely 11,069 MSMEs with various kinds of business units. The sample in this study was 100 samples using the Slovin formula. The data obtained from this study will be analyzed using multiple regression analysis. Based on the results of data analysis and discussion in the previous chapter, the following conclusions can be drawn. Accounting perceptions have no effect on the use of accounting information. So the higher the perception of accounting will not increase the use of accounting information for MSME actors. Accounting knowledge has a positive effect on the use of accounting information. Then the higher accounting knowledge will increase the use of accounting information by MSME actors. Business scale affects the use of accounting information. So the higher the scale of business by MSME actors will increase the use of accounting information by MSME actors. Keywords: (MSME Perception, Accounting Knowledge, Business Scale, Accounting Information)